PENINGKATAN PEMAHAMAN GEOMETRI TRANSFORMASI DENGAN PEMBELAJARAN E-LEARNING BERBASIS MASALAH KEARIFAN LOKAL - Khoiruddin Matondang; Ulfa Annisa Lubis; Risna Mira Bella Saragih; Melani Prasiska (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Students often have difficulty understanding the concept of transformation geometry because it is abstract and has little to do with the real context. One of the causes is less meaningful and non-contextual learning. Therefore, one of the efforts that can be made is based on local wisdom. On the other hand, e-learning as an educational innovation has been widely used, but its application has not been optimal, especially to explain visual and abstract concepts such as transformation geometry. Therefore, an e-learning approach is needed that integrates contextual problems based on local wisdom to improve student understanding. This study aims to discuss the effect of e-learning learning based on local wisdom problems on improving students' understanding of transformation geometry. The research was conducted at Al-Azhar High School Medan, the subject of class XII research was 146 students who were selected by random sampling to select samples. The type of research used was quasi-experimental with a pretest-postest control group design. Data collection used a transformation geometry understanding ability test, including indicators of translation, dilation, reflection and rotation. The significance value of the Independent Sample t Test 0.00 < 0.05 means that there is a significant difference in the increase (gain) of experimental students with the control class. Through these results, it can be concluded that e-learning based on local wisdom problems has an effect on improving students' understanding of transformation geometry. The results of the dilatation indicator gain were 0.51, translation 0.54, reflection 0.47, rotation 0.44 with each category moderate.